2012
DOI: 10.1016/j.immuni.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cells Recognize a Microbial Encoded B Cell Antigen to Initiate a Rapid Antigen-Specific Interleukin-17 Response

Abstract: Summary γδ T cells contribute uniquely to host immune defense. However, how they function remains an enigma. Although it is unclear what most γδ T cells recognize, common dogma asserts that they recognize self-antigens. While they are the major initial Interleukin-17 (IL-17) producers in infections, it is unclear what is required to trigger these cells to act. Here, we report that a noted B cell antigen, the algae protein-phycoerythrin (PE) is an antigen for murine and human γδ T cells. PE also stained specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
173
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(201 citation statements)
references
References 39 publications
14
173
0
Order By: Relevance
“…Intriguingly, DN3 cells expressed Bcl11b but lost the potential to develop IL-17-producing gd T cells (9, 10), suggesting the presence of an as yet unknown suppressive mechanism. Furthermore, a recent study showed that some gd T cells migrated to the peripheral tissues as naive cells and functionally differentiated to IL-17 producers after Ag encounter (44). It remains unclear whether the development of Aginduced IL-17-producing gd T cells from naive cells requires Bcl11b.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, DN3 cells expressed Bcl11b but lost the potential to develop IL-17-producing gd T cells (9, 10), suggesting the presence of an as yet unknown suppressive mechanism. Furthermore, a recent study showed that some gd T cells migrated to the peripheral tissues as naive cells and functionally differentiated to IL-17 producers after Ag encounter (44). It remains unclear whether the development of Aginduced IL-17-producing gd T cells from naive cells requires Bcl11b.…”
Section: Discussionmentioning
confidence: 99%
“…‘natural’ γδ 17 cells (V γ 6 + and part of V γ 4 + ) developed before birth acquire interleukin‐17 ( IL ‐17) ‐producing ability in thymus and produce IL ‐17 stimulated by IL ‐1 β and IL ‐23 in the periphery. Conversely, IL ‐17 production induced by TCR signalling was also reported 56. Naive γδ T cells developed after birth may egress the thymus as ‘inducible’ γδ 17 cells (mostly V γ 4 + ) and differentiate to produce IL ‐17 after encounter with antigen.…”
Section: γδ T‐cell Subsets and Their Developmentmentioning
confidence: 99%
“…Although γδ 17 cells typically behave as innate‐like immune cells, IL‐17 induction by TCR signalling is also reported. Mouse and human γδ T cells recognize an algal protein, phycoerythrin, and differentiate to IL‐17‐producing cells after immunization by this antigen 56. These studies, in combination with cell reconstitution studies,50 suggest that ‘natural’ γδ 17 cells (V γ 6 + and part of V γ 4 + ) acquire IL‐17‐producing ability in the fetal thymus and do not require TCR stimulation in the periphery, whereas ‘inducible’ γδ 17 cells (mostly V γ 4 + ) that develop after birth produce IL‐17 upon encounter with antigens57 (Fig.…”
Section: The Mechanism Of Il‐17 Production In γδ17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to conventional αβ T cells, γδ T cells are not dependent on classical MHC molecules presenting peptides. Based on the ligands that have been identified, it appears that some γδ TCRs can recognize antigens in an antibody-like fashion, whereas the TCRs of other γδ T-cell subsets can bind to nonclassical MHC-I or MHClike proteins (2,(5)(6)(7)(8)(9)(10)(11). Although there are common characteristics among γδ T cells, some of which are shared with VLRC + cells (4), it is clear that γδ T cells do not represent a homogenous population of cells with a single physiological role (12).…”
Section: Ike Conventional αβ T Cells and B Cells γδ T Cells Use V(d)jmentioning
confidence: 99%